Comparative Analysis of Different Display Technologies for Defect Detection in 3D Objects - Vasil Kozov; Ekaterin Minev; Magdalena Andreeva; Tzvetomir Vassilev; Rumen Rusev (Technologies)
This paper starts with an overview of current methods of displaying 3D objects. Two different technologies are compared—a glasses-free 3D laptop that uses stereoscopy, and one that uses front projection on a silver impregnated fabric screen that diffracts light to achieve a holographic effect. The research question is defined—which one is suitable for use by specialists. A methodology for an experiment is designed. A scenario for finding the solution to the problem during the experiment is created. An experiment environment with different workstations for each technology has been set up. An additional reference workstation with a standard screen has been created. Three-dimensional CAD models from the field of mechanical engineering were chosen. Different categories of defects were introduced to make the models usable for the scenario—finding the defects in each of the different workstations. A survey for participant feedback, using several categories of questions, was created, improved, and used during the experiment. The experiment was completed, short discussions were held with each participant, and their feedback was analyzed. The categories of the participants were discussed. The results from the experiment were discussed and analyzed. Statistical analysis was performed on the survey results. The applicability of the experiment in other fields was discussed. Conclusions were made, and the comparative advantages and specifics of each technology were discussed based on the analysis results and the experience gained during the experiment.